AVIFAUNAL DIVERSITY OF MALLATHAHALLI LAKE IN BANGALORE URBAN DT., KARNATAKA, INDIA - VIDYA PADMAKUMAR; C. SILAMBARASAN; SHINE P JOSEPH (The Bioscan, 2020)
The study was conducted from July 2015 to July 2017 to determine and understand the occurrence and diversity of avifauna in the Mallathahalli Lake of Bangalore Urban District. During the study period, 46 species of both terrestrial as well as aquatic birds belonging to 30 families were identified, of which 9 families were aquatic birds and 21 families were terrestrial birds. There were 4 species of migratory birds out of 46, showing diurnal migration. There was a significant reduction in the number of bird species both terrestrial and aquatic during the summer season and also varied greatly during winters and monsoons. Of the total 24 species of aquatic birds, Fulica atra and Tachybaptus ruficolis was the most common and the least common Threskiornis melanocephalus. Among the 22 species of terrestrial birds, Acridotheres tristis was the most common and the least frequent was Pycnonotus cafer. The most commonly encountered bird species were from the families Anatidae, Podicipedidae, Ardeidae, Phalacrocoracidae, Rallidae, Accipitridae, Scolopacidae, Charadridae, Laridae, Meropidae and Hirudinidae. All the birds surviving around the area, live dependent on the wetland and crop vegetation surrounding the lake, and anthropogenic interventions are gradually causing a decline in avifaunal diversity which must be monitored further and protected.